Integration of PCM as an external wall layer in reducing excessive heat of building walls - Nor Ali U.N.; Mohamad Nor N.; Misnon N.A.; Mohd Noor S.A.; Othman M.; Alias M.A.A.; Syamsir A. (Institute of Physics, 2023)
Air conditioning; Atmospheric temperature; Energy management; Energy utilization; Paint; Phase change materials; Plaster; Surface properties; Walls (structural partitions); Air conditioner; Building walls; Energy demands; External surfaces; External walls; Indoor thermal comfort; Painted walls; Phase change material; Surface temperatures; Wall panels; Latent heat